Chemotactic disruption as a method to control bacterial wilt caused by Ralstonia pseudosolanacearum. Issue 3 (31st December 2020) - Tunchai, Mattana; Hida, Akiko; Oku, Shota; Tajima, Takahisa; Kato, Junichi
ABSTRACT: We have demonstrated that chemotaxis to l -malate facilitated motility of Ralstonia pseudosolanacearum MAFF 106611, a causative agent of bacterial wilt, to plant roots. Here, we evaluated the assumption that the disruption of chemotaxis to l -malate leads to inhibition of plant infection by R. pseudosolanacearum MAFF 106611. Chemotactic assays revealed that chemotaxis to l -malate was completely or partially inhibited in the presence of l -, d -, and dl -malate, respectively. Moreover, l -malate served as a carbon and energy source for R. pseudosolanacearum MAFF 106611, while d -malate inhibited the growth of this bacterium. In the sand-soak inoculation virulence assay for tomato plants, the addition of l -, d -, and dl -malate to sand suppressed the plant infection. We concluded that supplementation of l - and dl -malate suppresses tomato plant infection with R. pseudosolanacearum MAFF 106611 by disrupting its chemotaxis to l -malate, while d -malate suppresses it by both the disruption of l -malate chemotaxis and inhibition of growth. Graphical Abstract: